2014
DOI: 10.3109/0142159x.2014.920952
|View full text |Cite
|
Sign up to set email alerts
|

Teaching behaviors that define highest rated attending physicians: A study of the resident perspective

Abstract: The most effective teaching behaviors fell into two broad domains: Teaching Process and Learning Atmosphere. Highest rated attending physicians are most recognized for characteristics in the Teaching Process domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Preliminary data from a qualitative study of resident and medical students' perceptions of faculty teaching did reveal differences between the two levels of learners, with residents appearing to value efficiency more than the students in that study. 20 Future studies should further compare how medical students and residents perceive differences in effective clinical teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data from a qualitative study of resident and medical students' perceptions of faculty teaching did reveal differences between the two levels of learners, with residents appearing to value efficiency more than the students in that study. 20 Future studies should further compare how medical students and residents perceive differences in effective clinical teaching.…”
Section: Discussionmentioning
confidence: 99%
“…The second component of the curriculum consisted of preceptor modeling. Modeling is an effective teaching technique that improves learner skills and competencies and is associated with high rates of resident satisfaction ( Huff et al, 2014 ). Preceptors identified specific scenarios and modeled, either in the examination room or while precepting, how they would review topics with the family using the EBCTs featured in the didactic training.…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly true in neurology, where the majority of students witness at least one difficult conversation about new disability or prognosis during their clerkship and residents participate in such conversations regularly. 36 Multiple studies have demonstrated role modeling to be among the most appreciated traits in highly respected clinical teachers, 16,19 though this is not uniformly the case. 29 Excellent clinical teachers consider this responsibility important and make conscious choices about which traits to model and how.…”
Section: Practical Advantagesmentioning
confidence: 99%
“…7,[9][10][11][12][13][14][15] Yet, the bedside is considered by teachers and learners alike to be an effective locale for teaching the history, physical exam, and humanistic aspects of medicine. 8,[15][16][17][18][19][20][21][22][23][24] Moreover, most patients and families feel positively about being involved in bedside teaching. [25][26][27] Bedside teaching has previously been defined broadly as "clinical teaching in the presence of a patient," 8 which must be distinguished from "door-jamb" or "corridor" teaching.…”
mentioning
confidence: 99%